A Note on Constant Mean Curvature Foliations of Noncompact Riemannian Manifolds - S. Ilias; B. Nelli; M. Soret (International Journal of Mathematics and Mathematical Sciences)
We aimed to study constant mean curvature foliations of noncompact Riemannian manifolds, satisfying some geometric constraints. As a byproduct, we answer a question by M. P. do Carmo (see Introduction) about the leaves of such foliations.